ANALISIS REPRODUKSI KELINCI PERSILANGAN NEW ZEALAND WHITE DI KABUPATEN BLITAR - Putri Rahayu; Agustina widyasworo; Nita opi ari kustanti (Universitas Islam Balitar, 2019)
This research was conducted with the aim of knowing the reproduction of rabbit crosses in Blitar. The method used analysis quantitative descriptive the purpose is to describe the file. The research describe,deviation standart, highest and lowelst values. This research material uses rabbit crosses with the same maintenance and feeding systems that have at least given birth to litter size, service per conception, and birth interval. The results obtained from this study to show an average litter size of 6 owned, service per conception of 2 times marriage and birth interval 2 months.